Using COBIT 2019 SME for Digital Transformation Governance of BPRDCo - Rashikha, Nai`la; Mulyana, Rahmat; Hanafi, Ridha (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
Globalization has driven incumbent organizations to innovate through digital transformation (DT) to stay relevant. However, many DT efforts fail due to inadequate IT Governance (ITG). Ambidextrous ITG models using COBIT 2019 framework have demonstrated effectiveness in large banks. However, their applicability to small enterprises remains unexplored. This research aims to develop a prioritized ITG solution for SME and estimate the capability improvement of its maturity level for successful DT. The research followed five stages of Design Science Research (DSR), using COBIT 2019â€™s SME focus area identified three key IT Governance and Management (ITGM) objectives: APO12 (Managed Risk), APO13 (Managed Security), and MEA03 (Compliance with External Requirements), with an average capability maturity level of 3.17. Thirteen essential solutions are recommended and compiled into an implementation roadmap, targeting a capability level increase to 3.86. This research contributes to ITG knowledge for DT at the SME level and practical implications for similar organizations.Keywords: Digital Transformation; Design Science Research; IT Governance; COBIT 2019 SME Focus Area; Bank.Â AbstrakGlobalisasi telah mendorong organisasi untuk berinovasi melalui Transformasi Digital (TD) agar tetap relevan. Namun, banyak upaya TD gagal karena Tata Kelola TI (TKTI) yang tidak memadai. Model TKTI hibrida yang menggunakan kerangka kerja COBIT 2019 telah menunjukkan efektivitas di bank-bank besar. Namun, penerapannya untuk usaha kecil masih belum dieksplorasi. Tujuan penelitian ini adalah untuk mengembangkan solusi TKTI yang diprioritaskan untuk UKM dan memperkirakan peningkatan kemampuan tingkat kematangannya untuk keberhasilan TD. Penelitian ini mengikuti lima tahap Design Science Research (DSR), menggunakan COBIT 2019 Area Fokus SME mengidentifikasi tiga tujuan utama Tata Kelola dan Manajemen TI (TKMTI): APO12 (Managed Risk), APO13 (Managed Security), dan MEA03 (Managed Compliance with External Requirements), dengan tingkat kematangan kemampuan rata-rata 3,17. Tiga belas solusi penting direkomendasikan dan disusun ke dalam roadmap implementasi, menargetkan peningkatan tingkat kemampuan menjadi 3,86. Penelitian ini berkontribusi pada pengetahuan TKTI untuk TD di tingkat UKM serta implikasi praktis untuk organisasi serupa.Â